Available Opportunities of the Formation of Information Culture of the Pupils of Azerbaijani Schools Through the Use of ICT (Journal of Educational Sciences, 2017)
The authors, noting the increased influence of technology on society in the modern age and the preference of young generation electronic information resources, instead of reading books, justify the need for the modern teacher ownership of new information and computer technologies of training. According to the authors, the coexistence of traditional teaching methods and modern information technologies, and the use of computer can help teachers in solving complex problems of teaching in the information age. Referring torecent studies carried out in Azerbaijan, the authors prove that the attitude towards education in the country has changed in schools and in the education system as a whole: the teaching and learning process is now closely linked to technologization of the modern education system. In this regard, the authors reveal the essence of the concept “information culture” in the context of modern developments of the Azerbaijani researchers. The following section discusses the process of using ICT in lessons at school. For example, is working with the educational blog on biology, created in Facebook in Azeri language. The blog functioned primarily as an online diary, and later transformed into the site helped the teachers in Information-rich lesson, and students in receiving the latest scientific information on the subject.
Keywords: information culture; ICT; education; the Internet; information society; school; computer; pupil; social network; teacher